A correlation between tocopherol content and antioxidant activity in seeds and germinating seeds of soybean cultivars. (4th December 2014) - Lee, Yu Young; Park, Hyang Mi; Hwang, Tae Young; Kim, Sun Lim; Kim, Mi Jung; Lee, Seuk Ki; Seo, Min Jung; Kim, Kee Jong; Kwon, Young‐Up; Lee, Sang Chul; Kim, Yul Ho
Abstract BACKGROUND Tocopherols are crucial lipid‐soluble antioxidants and essential nutrients. There is increasing interest in the biofortification of crops with vitamin E for reducing micronutrient malnutrition. However, relatively little is known about the development of soybean cultivars with high levels of tocopherol through combined breeding. RESULT Tocopherol contents of seeds and germinating seeds of 28 Korean soybean cultivars were analyzed and evaluated for health‐promoting activities. Total tocopherol concentrations ranged from 203.9 to 503.1 µg g−1 in seeds and from 20.1 to 230.1 µg g−1 in germinating seeds. The traditional landraces of HaNagari (HN, 503.1 µg g−1), Orialtae (OL, 486.6 µg g−1), SuMoktae (SM, 476.5 µg g−1) and SoRitae (SR, 475.5 µg g−1) showed high levels of tocopherol content. The contents of the four isomers of tocopherol in seeds and germinating seeds were correlated with lipid peroxidation. The γ‐ and δ‐tocopherol contents in seeds were related to 1, 1‐diphenyl‐2‐picrylhydrazyl free radical scavenging activity (0.434; P < 0.01 and 0.373; P < 0.05). CONCLUSION Total tocopherol content was higher in soybean landraces as compared with modern cultivars developed by cross‐breeding. These results suggest that soybean breeding is necessary to increase tocopherol levels. © 2014 Society of Chemical Industry